2003
DOI: 10.1677/erc.0.0100261
|View full text |Cite
|
Sign up to set email alerts
|

How to target estrogen receptor-negative breast cancer?

Abstract: Estrogen receptor (ER)-positive breast cancers generally have a better prognosis and are often responsive to anti-estrogen therapy, which is the first example of a successful therapy targeted on a specific protein, the ER. Unfortunately ER-negative breast cancers are more aggressive and unresponsive to anti-estrogens. Other targeted therapies are thus urgently needed, based on breast cancer oncogene inhibition or suppressor gene activation as far as molecular studies have demonstrated the alteration of express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 40 publications
(30 reference statements)
1
58
0
1
Order By: Relevance
“…On the other hand, in ERa-negative MDA-MB-231 cells with forced ERa expression, FOXA1 activated the ER pathway, leading as well to slowed growth. 23 These findings thus further support a growth inhibitory role for FOXA1 in breast cancer. Cell-type dependent transcriptional activity of FOXA proteins is not unique for breast cancer and has also been demonstrated in hepatoma and neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…On the other hand, in ERa-negative MDA-MB-231 cells with forced ERa expression, FOXA1 activated the ER pathway, leading as well to slowed growth. 23 These findings thus further support a growth inhibitory role for FOXA1 in breast cancer. Cell-type dependent transcriptional activity of FOXA proteins is not unique for breast cancer and has also been demonstrated in hepatoma and neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 54%
“…23 We found that trans- Low FOXA1 (N, %) 5 (6) 11 (14) 12 ( fection of the ERa into MDA-MB-231 cells resulted in upregulation of FOXA1 protein levels (Fig. 3b).…”
Section: Differential Transcriptional Regulation Of the Ere By Foxa1mentioning
confidence: 79%
“…Whereas ER-positive tumors tend to be localized and respond well to hormonal manipulation (26), ER-negative tumors are more aggressive, disseminate widely, and do not respond to hormone therapy (5). A number of mechanisms for the development of ERa negativity have been identified (27)(28)(29)(30)(31)(32). This includes hypermethylation of the ERa promoter in f60% of cases (33) and repression by transcription factors such as pRB2/p130 and LMO4 (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…40 Future directions of our work will be to include and individualize the value of protease measurement in the case of adjuvant chemotherapy and endocrine therapy, in order to select patients according to their prognostic risk, as proposed in NNBC3 trial. In particular, some studies have suggested that cath-D inhibitors might also potentially be capable of reversing anti-estrogen resistance in ER-positive BC that overexpress cath-D.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%